FINANCIAL LITERACY EDUCATION FOR SME BUSINESS ACTORS IN IMPROVING FINANCIAL MANAGEMENT AT MUHAMMADIYAH CHARITY WARUNG SOTO LAMONGAN IN KUALA LUMPUR, MALAYSIA - Dwi Wahyuni, Endang; Leniwati, Driana (International Journal of Engagement and Empowerment (IJE2), 2023)
This community service activity aims to increase knowledge about financial literacy for UKM, namely increasing the understanding of some Muhammadiyah citizens in Malaysia regarding financial planning and improving the quality of preparing financial reports for UKM Muhammadiyah Charity Warung Soto Lamongan (WASOLA) in planning their finances. With this service activity on financial literacy, AUM can make financial plans and prepare good and accurate financial reports. This activity is carried out by conducting outreach on financial literacy and financial management training. The target of this activity is the Muhammadiyah Charity Business Warung Soto Lamongan in Kuala Lumpur. The output resulting from this service is increasing managers' understanding of financial literacy, increasing awareness of financial management and implementing financial report preparation programs that are appropriate to partners' conditions. The financial reporting application that will be provided to partners is an Excel-based application, which is quite simple, easy to apply and can solve partner problems. This application is designed to be used by anyone